The Modernist trading store in KwaZulu-Natal as evocative material culture - Whelan, D. (Southern African Humanities, 2017)
From the 1950s onwards, a Modernist architectural paradigm characterized many trading store buildings in KwaZulu-Natal, South Africa. In contrast with the vernacular buildings that formed the majority of the early trading stores, these latter-day examples have formed the basis of the architectural toolkits that comprise contemporary African-owned community shops or spazas offering a much reduced level of trade in rural areas. These post-1994 structures are constructed in the image of the old and successful trading stores, suggesting a transfer of architectural idiom that transcends commonly constructed ideas of power and domination and offers a very different view of a past social landscape and the relations between traders and their customers. This paper discusses the architectural frameworks, examines the encoding of the trading store and recoding into the spaza shop, as well as its lodgment in memory. The Modernist trading store and its offspring, the spaza, have an embedded visceral recognition, connoting different ideas and memories and culminating in the suggestion that these structures comprise anamnestic repositories in the South African landscape.